Estudo de associação genômica e perfil de expressão gênica de folículos antrais em novilhas das raças nelore e angus, associadas ao fenótipo de alta e baixa população folicular - Favoreto, Maurício Gomes [UNESP] (2015)
Animals with high antral follicle count (HFC) have a better reproductive performance when compared with animals with low follicle count (LFC). This variation in the number of antral follicles can be associated with different hormonal profiles and expression of genes regulating activation and follicular growth. The objective of the present work was: 1) to evaluate the global gene expression of antral follicles in animals with HFC and LFC in Nelore (Bos indicus) and Aberdeen Angus (Bos taurus) heifers and 2) to identify genotypic differences through a genomic wide association study (GWAS) using single nucleotide polymorphisms (SNP). Initially, 155 Nelore heifers and 132 Angus heifers with similar body weight and age were selected. The animals were synchronized and follicle count was done through ultrasound 24 to 48 h after estrus. The groups LFC and HFC were formed using the average of follicles ± standard deviation in both breeds. To evaluate the global gene expression profile we use a microarray chip. A total of 15 Nelore heifers (6 HFC and 9 LFC) and 17 Angus heifers (9 HFC and 8 LFC) were slaughter 12 to 24 h after ovulation and ovaries were transported to the laboratory. A pool of RNA from three follicles (< 4 mm) from each animal was used to the analysis using FlexArray 1.6.1.1 and the genes with fold change > 1.5 and P ≤ 0.05 were considered differentially expressed. For the GWAS study 72 Nelore heifers (32 HFC and 40 LFC) and 48 Angus heifers (21 HFC and 27 LFC) were selected. The DNA was extracted from blood and hair bulb and genotyping was done using the 777 HD Illumina chip. The SNPs were submitted to a quality control test using an exclusion criteria: call rate (IDCR) ≤ 90%, MAF ≤ 0.02, call rate (SNPCR) ≤ 0.98 and HWE ≤ 1 x 10-5. After the quality control test the SNPs were submitted to the Cochran-Armitage test to the association of phenotype/genotype in both breeds. The genes differentially expressed and the genes ...